Going beyond the curve: Strategic measures to recover hotel activity in times of COVID-19 - Garrido-Moreno, Aurora; García-Morales, Víctor J.; Martín-Rojas, Rodrigo (Elsevier, 2021)
Hospitality firms are facing unprecedented challenges on a global scale. The catastrophic effects of the COVID-19 pandemic and its multiple devastating global consequences have initiated a profoundly disruptive transformation in the hospitality sector, as firms attempt to adapt their activity to the current uncertain scenario. This study draws on the crisis management literature to identify the key drivers of hotel recovery in the event of a disaster or an external crisis, like current pandemic. A sample of 237 Spanish hotel managers evaluated and ranked the strategic measures. Based on this evidence, measures were statistically examined to identify which ranked as most significant in helping hospitality managers. The results yield valuable theoretical and practical insights to guide hospitality managers towards business adaptation and recovery by highlighting key strategic measures for implementation in the short term.
Keywords: COVID-19; Hostelería; Strategic measures; Hotels; Crisis management